2018
DOI: 10.33366/cr.v6i3.953
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Kombinasi Sugesti Dan Dzikir Dalam Peningkatan Kualitas Tidur Pasien

Abstract: Kebutuhan istirahat masing-masing individu berbeda dipengaruhi oleh status kesehatan pada individu, pola aktivitas, gaya hidup, usia serta kualitas tidur. Pemberian terapi non farmakologi dapat dilakukan untuk mengatasi gangguan tidur, dengan modifikasi perilaku dan lingkungan. Pemberian sugesti melalui hipnoterapi, bentuk intervensi relaksasi juga dapat dilakukan dengan melakukan dzikir yang merupakan bentuk memasrahkan diri kepada Allah SWT. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian terap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The findings of this study prove that zikr asmaul husna as a psychotherapeutic method can improve sleep quality in schizophrenic clients at UPT Rehabilitasi Sosial Bina Laras Kediri. This is in accordance with several previous studies conducted by Syaifurrahman Hidayat and Elyk Dwi Mumpuningtias entitled "Combination Therapy of Suggestion and Remembrance in Improving the Quality of Patient Sleep" which obtained the results of suggestion and remembrance in improving the quality of sleep of patients who are undergoing treatment at the hospital will affect the patient's subconscious condition so that it is easier for patients to enter a state of relaxation (Hidayat & Mumpuningtyas, 2018) Nashori, (2011) revealed that the condition of the liver is also an aspect of sleep where with sleep the condition of one's heart becomes peaceful. Good sleep makes a person feel comfortable and happy, and poor sleep makes a person easily tired, irritable, and the causes of depression.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study prove that zikr asmaul husna as a psychotherapeutic method can improve sleep quality in schizophrenic clients at UPT Rehabilitasi Sosial Bina Laras Kediri. This is in accordance with several previous studies conducted by Syaifurrahman Hidayat and Elyk Dwi Mumpuningtias entitled "Combination Therapy of Suggestion and Remembrance in Improving the Quality of Patient Sleep" which obtained the results of suggestion and remembrance in improving the quality of sleep of patients who are undergoing treatment at the hospital will affect the patient's subconscious condition so that it is easier for patients to enter a state of relaxation (Hidayat & Mumpuningtyas, 2018) Nashori, (2011) revealed that the condition of the liver is also an aspect of sleep where with sleep the condition of one's heart becomes peaceful. Good sleep makes a person feel comfortable and happy, and poor sleep makes a person easily tired, irritable, and the causes of depression.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the opinion expressed by Reswandi & Sunarsi [28] which states that suggestions can change a person's behavior. This opinion is also corroborated by the results of research conducted by Cahyadi [29], Hidayat & Mumpuningtias [30], and Ibrahim [31] that found suggestions have a significant effect on increasing motivation in dealing with problems, improving behavior, and improving quality of life. It is in such a context that sembek is expected to play a role in dealing with the COVID-19 outbreak.…”
Section: B Discussionsupporting
confidence: 65%
“…The selfdefense mechanism of the elderly who are not strong in dealing with problems will cause prolonged stress and eventually symptoms of depression will arise. 20 According to Stuart & Laraia (2005) explains that emotional support can be given in the form of motivating the confidence of the elderly in dealing with the problems they face.…”
Section: Discussionmentioning
confidence: 99%